Token Based Authentication Using IOT - Hegade, Akshay; Sindhu, KG (International Journal of Computer Sciences and Engineering, 2019)
Token Based Authentication is one of the basic mechanism of login that will be required and used in most of the web applications. The token is prima focus in the whole functionality of the product which can not be decrypted by users.